Hebrew books from the Harvard College Library : index to the microfiche collection - Berlin, Charles, 1936- (K.G. Saur, 1996)
Index to microfiche collection of 4,934 titles filmed on 11,453 microfiche. It is divided into three sections: Author/Title, Subject and Imprint.